Workplace loneliness and job performance of employees: The role of burnout and affective commitment - Phan Quoc , Tan (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2024)
Although workplace loneliness has a negative impact on job performance of employees, studies on the effects of workplace loneliness on job performance through its mediating role of burnout and affective commitment have still received relatively little attention. Based on the Conservation of Resources (COR) and Social Exchange Theory, research on the effects of workplace loneliness, burnout, and affective commitment on the job performance of employees in the Export Processing Zones Ho Chi Minh City (EPZ HCMC). A survey of 351 employees in the EPZs of HCMC was conducted, and the results of the structural equation modeling tests show that all relationships are significant. Furthermore, burnout and affective commitment partially mediate the relationship between workplace loneliness and job performance. Besides, there are differences by gender, age, and seniority in the relationship between workplace loneliness and burnout, affective commitment, and job performance. Therefore, this study has new theoretical contributions and some management implications to improve the job performance of employees in the EPZ HCMC.